Upper extremity musculoskeletal characteristics and the Kerlan-Jobe Orthopaedic Clinic Questionnaire Score in collegiate baseball athletes - Faherty, M. S.; Plata, A.; Chasse, P.; Zarzour, R.; Sell, T. C (Journal of Athletic Training, 2019)
Context Upper extremity (UE) musculoskeletal injuries are common in baseball athletes due to the increased demand placed on the UE. The link between risk factors for UE musculoskeletal injuries and baseball athletes' perceived UE function and pain, as measured by the Kerlan-Jobe Orthopaedic Clinic (KJOC) questionnaire, is unclear.